Biomass removal by clipping and raking vs burning for the restoration of abandoned Stipa‐dominated European steppe‐like grassland. Issue 1 (27th August 2015) - Ruprecht, Eszter; Enyedi, Márton Zsolt; Szabó, Anna; Fenesi, Annamária
Abstract: Question: Do restoration measures involving yearly biomass removal over 9 yr have a beneficial effect on the structure and composition of long‐term abandoned European steppe‐like grassland? What is the effect of a single accidental fire event on this grassland community? Location: Continental dry steppe‐like grassland, Suatu and Puini, Transylvania, Romania. Methods: In two long‐term abandoned grassland sites, we experimentally carried out annual biomass removal by clipping and raking, and by raking alone over a period of 9 yr. We analysed the effect of the two planned treatments in both sites and that of an accidental fire in one of the sites on the structure and composition of vegetation. We applied a predominantly functional trait‐based analysis, but the dominant species Stipa pulcherrima and Carex humilis were treated separately. Results: Annual biomass removal applied for 9 yr at one site favoured sub‐dominant grasses and short‐lived forbs over long‐lived forbs and the two dominant species, and generated a successional shift to more open grassland. The clipping and raking treatment promoted plot‐scale species richness when the grassland species pool was large enough. The number and abundance of Red‐Listed species were not influenced by our treatments. The single accidental fire event at one of the sites negatively affected the two dominant species and promoted one of the sub‐dominant grasses. In addition, burning in combination with abandonment and presence of stoloniferous grass species benefiting from fire decreased species richness. Variation in weather conditions, in particular the series of dry years during our experiment, caused significant changes in vegetation cover and the quantity of litter, and decreased the abundance of S. pulcherrima in both sites and that of long‐lived forbs in one site. Conclusions: According to our results, biomass removal had a beneficial effect on vegetation structure and composition in long‐term abandoned steppe‐like grassland. Until further experimental data on the effect of burning on temperate dry grassland are available, traditional management practices should be favoured over alternative methods. Abstract : We experimentally investigated if yearly biomass removal by clipping and raking have a beneficial effect on the long‐term abandoned steppe‐like grassland, and if fire is a good alternative. Clipping and raking had a beneficial effect on vegetation structure and composition and lead to more open grassland. A single fire event negatively affected the dominant species and promoted a stoloniferous grass.